2017
DOI: 10.1093/brain/awx002
|View full text |Cite|
|
Sign up to set email alerts
|

Deleterious variants in TRAK1 disrupt mitochondrial movement and cause fatal encephalopathy

Abstract: Cellular distribution and dynamics of mitochondria are regulated by several motor proteins and a microtubule network. In neurons, mitochondrial trafficking is crucial because of high energy needs and calcium ion buffering along axons to synapses during neurotransmission. The trafficking kinesin proteins (TRAKs) are well characterized for their role in lysosomal and mitochondrial trafficking in cells, especially neurons. Using whole exome sequencing, we identified homozygous truncating variants in TRAK1 (NM_001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…Mutations in Opa1 cause autosomal-dominant optic atrophy, a disease of progressive blindness due to degeneration of retinal ganglion cells, but which can also include more widespread neuronal degeneration (Alexander et al, 2000; Chen and Chan, 2006; Delettre et al, 2000; McFarland et al, 2010). Truncations of the human milton isoform TRAK1 cause fatal encephalopathy (Barel et al, 2017). As indicated above, the most common mitostatic disease identified to date is Parkinson’s disease.…”
Section: Mitostatic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in Opa1 cause autosomal-dominant optic atrophy, a disease of progressive blindness due to degeneration of retinal ganglion cells, but which can also include more widespread neuronal degeneration (Alexander et al, 2000; Chen and Chan, 2006; Delettre et al, 2000; McFarland et al, 2010). Truncations of the human milton isoform TRAK1 cause fatal encephalopathy (Barel et al, 2017). As indicated above, the most common mitostatic disease identified to date is Parkinson’s disease.…”
Section: Mitostatic Diseasesmentioning
confidence: 99%
“…Mitofusin2 mutations cause Charcot-Marie-Tooth disease type 2A (Kijima et al, 2005; Zuchner et al, 2004) and Opa1 mutations are responsible for autosomal dominant optic atrophy (Alexander et al, 2000; Delettre et al, 2000; McFarland et al, 2010). Mutations of Drp1, MFN, and Trak1 (Milton) are very rare in humans, but cause early lethality with broad defects that include neurological symptoms such as fetal encephalopathy and optic atrophy (Barel et al, 2017; McFarland et al, 2010). …”
Section: Introduction: Mitostasis In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the formation of the TRAK1-kinesin adaptor is inhibited in axons of hippocampal pyramidal neurons, mitochondrial mobility is decreased (Brickley and Stephenson, 2011). Furthermore, TRAK1 depletion leads to mitochondrial fragmentation (Lee et al, 2017) and a recent report identified mutations in the TRAK1 gene in individuals with neurodevelopmental delay, seizures, and fatal encephalopathy (Barel et al, 2017). Fibroblasts derived from these individuals exhibit damaged mitochondria distribution due to impaired mitochondrial motility and reduced respiration capacity (Barel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TRAK1 depletion leads to mitochondrial fragmentation (Lee et al, 2017) and a recent report identified mutations in the TRAK1 gene in individuals with neurodevelopmental delay, seizures, and fatal encephalopathy (Barel et al, 2017). Fibroblasts derived from these individuals exhibit damaged mitochondria distribution due to impaired mitochondrial motility and reduced respiration capacity (Barel et al, 2017). Still, the function of TRAK1 in cardiac and skeletal muscle tissue has not been described.…”
Section: Introductionmentioning
confidence: 99%